The Effect of Social Media Live Streaming and Promotion on Online Purchase Intention in The TikTok @Daydeals.Co - Suhendar, Nicky Christian; Murdiani, Trufi (Proceeding International Conference on Information Technology and Business, 2023)
This study explores how social media live streaming and promotions on the TikTok platform, with a focus on the @Daydeals.Co account, impact online purchase intentions. Using a quantitative approach, questionnaires are distributed to followers, with independent variables including live streaming interactions and @Daydeals.Co's promotional strategies, and the dependent variable being respondents' online purchase intentions. Employing regression analysis, the research aims to uncover the extent to which these factors influence online purchasing. The findings are expected to provide valuable insights for digital marketers and business owners, aiding them in maximizing TikTok's potential as an effective marketing channel. The practical implications include helping companies understand consumer behavior in the digital era and refining online marketing strategies, especially on live streaming platforms like TikTokKeywords: live streaming, digital content, tiktok.